United States : Background Papers. (IMF Staff Country Reports; Country Report ;, 1995)
This Background Paper on the United States examines the effect of fiscal deficit reduction in the context of the IMF's multicountry simulation model, on the current account and the real exchange rate. The simulations suggest that, other things being equal, fiscal consolidation will tend to cause the real exchange rate to depreciate in the short term. The paper also estimates a long-term relationship between the real effective exchange rate for the U.S. dollar and a number of variables.